Feeding habits of Anoura geoffroyi (Chiroptera: Phyllostomidae) in Ixtapan del Oro, Mexico State. - Caballero-Martínez, Luis Antonio; Rivas Manzano, Irma Victoria; Aguilera Gómez, Luis Isaac (Instituto de Ecología, A.C., 2009)
We describe the feeding habits of the bat Anoura geoffroyi in the Seasonal Dry Tropical Forest at Ixtapan del Oro, Estado de Mexico. During a year, hair remainders and fecal samples from 153 individuals were collected every two weeks. We found just pollen grains and insect’s debris in the samples. The pollen morphotypes correspond to plants that are frequently visited for nectar-feeding bats, the genus Ipomoea outstands for its frequency and it is the first report of Brugmansia candida, Stenocereus sp. and a species from Asteraceae family in the A. geoffroyi diet. The plants determined from pollen morphotypes present chiropterophilous syndrome characteristics, nevertheless, they are also pollinated by moths. Reason why and considering the morphological adaptations of A. geoffroyi for nectar consumption and the fact that 95% of the insects debris found in the samples correspond to lepidopterons, we could consider the species in the study place like a nectar-feeding bat that also has the capacity to eat lepidopterons associated to the flowers where this bat forages.